Criminal Liability Arising from Contaminated Blood Transfusion - Mohammed Abdul Rahman , Lect. Dr. Makki (Basra studies journal, 2026)
This study examines the criminal liability arising from contaminated blood transfusion, which represents a complex legal and medical issue affecting the right to life and bodily integrity. The study reviews the conceptual framework of blood and its components, as well as the legal and technical regulations governing blood banks and healthcare institutions to ensure the safety of transfusions. It also focuses on the legal classification of serious professional errors that may be committed by physicians or laboratory personnel and analyzes the elements of criminal liability resulting from the transmission of infection, whether caused by negligence or failure in testing and storage procedures. The study concludes by identifying the penalties prescribed in Arab legislation for such acts and emphasizes the need to strengthen oversight and update medical and legal protocols to address emerging risks in this field.